Cyclosporine-based immunosuppressive therapy for patients with steroid-resistant focal segmental glomerulosclerosis: a meta-analysis. (3rd August 2017) - Chiou, Yuan-Yow; Lee, Yi-Che; Chen, Mei-Ju
Abstract: Objective: Focal segmental glomerulosclerosis (FSGS) is a leading cause of end-stage kidney disease that requires immunosuppressive treatment as therapy. Few studies have been specifically designed to assess the efficacy of cyclosporine (CSA) in patients with steroid-resistant FSGS. This study investigated the efficacy of CSA-based therapy in steroid-resistant FSGS. Methods: Medline, Cochrane, EMBASE, and Google Scholar databases were searched through April 30, 2014 using the keywords "cyclosporine", "steroid-resistant", "focal segmental glomerulosclerosis", and "FSGS". Studies with an adult and children with steroid-resistant primary FSGS treated with CSA-based therapy with or without steroid use were included. Complete, partial, and overall remission were the primary outcomes. Change in proteinuria, serum creatinine, and estimated glomerular filtration rate (eGFR) following treatment were secondary outcomes. Results: Seven randomized controlled trials with a total of 373 patients were included. Five studies were included in the meta-analysis to assess complete, partial, and overall remission of FSGS. Compared with other treatments, CSA-based therapy resulted in a significantly greater partial remission rate ( p  = .018), but complete ( p  = .226) or overall remission rate ( p  = .050). CSA-based therapy also resulted in similar change in proteinuria ( p  = .084), serum creatinine ( p  = .772), and eGFR ( p  = .155) compared with other therapy. Study limitations included small sample size and heterogeneity in age and comparative treatments across the studies. Conclusions: Cyclosporin-based treatments provided a significantly better partial remission rate as compared with other therapies.